The male sexuality and the vulnerability to HIV/Aids - Andrade, Laurinete S; Nóbrega-Therrien, Sílvia Maria (Brazilian Journal of Sexually Transmitted Diseases, 2005)
Introduction: the epidemic of the aids characterized by a changeable character and an overpowering effect on the human health at the same time.The epidemiological context suffers changes and the male and heterosexual population increase between the people who is affected by HIV. Thisway, this is necessary to understand also the factors that are responsible for the men have became susceptible of aids. Objective:to analyze the socialrepresentations about sexuality elaborated by men who are identified as heterosexual and their relation with the epidemic context of the aids.Methods:the approach of the study is the qualitative research .The researched men are older than eighteen that are identified as heterosexual. Themen assistance occurs at a reference center in DST in Fortaleza. It was used interview in order to colet the information. The data were examined bythe technic of contents analysis. Results: the representations found by the contents analysis reveal that their sexuality is presented as sex and that thisis considered out of control between the men for the natural condition. In despite of they considerer themselves susceptible e and they associate aidsto death, it appears distant from the real life. The use of the preservative appears as a way of preventing, but it reveals a painful and difficult process,considering that there is an interference in the sexual pleasure. Conclusion: the discoveries reveal the necessity of working the male sexuality as ahistorical and social construction. This comprehension is necessary for the implementation of the strategies of prevention to HIV-aids.